Optimization of electric and magnetic field emissions produced by independent parallel overhead power lines - Ranković Aleksandar; Mijailović Vladica; Rozgić Dimitrije; Ćetenović Dragan (Serbian Journal of Electrical Engineering, 2017)
This paper presents a method for determining optimal arrangements of parallel independent overhead power lines aimed to decrease electric and magnetic field emissions. The Genetic Algorithm (GA) is used to find the optimal placement of conductors. The Monte Carlo approach implemented in GA allows consideration of uncertain phase shifts between independent overhead power lines. The results and practical aspects of the proposed methodology are illustrated on two different configurations of both independent 400 kV singlecircuit and double-circuit overhead power lines. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. III-42009]